2011
DOI: 10.1177/0193945911407524
|View full text |Cite
|
Sign up to set email alerts
|

Project Wings, a Coping Intervention for Latina Adolescents

Abstract: The authors examined the feasibility and preliminary outcomes of Project Wings Girls' Groups, a school-based mental health promotion program designed to improve well-being in Latina adolescents, as observed in outcomes, including perceived stress, depressive symptoms, coping, and connectedness. This pilot randomized controlled trial compared outcomes over 9 months postintervention for 42 9th and 10th grade adolescents attending two urban high schools. Girls were randomized to Project Wings Girls' Groups, a 16-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…After title/abstract review, 36 were selected for full article review. After full review of these articles, 25 were eliminated because they did not meet the inclusion criteria that had been established for this systematic review. After reference lists of relevant articles were searched, an additional 3 articles were selected to be part of the review.…”
Section: Resultsmentioning
confidence: 99%
“…After title/abstract review, 36 were selected for full article review. After full review of these articles, 25 were eliminated because they did not meet the inclusion criteria that had been established for this systematic review. After reference lists of relevant articles were searched, an additional 3 articles were selected to be part of the review.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, nurses should seek to understand the stressors and factors in the lives of an adolescent that are contributing to an adolescent having a negative mood. Existing adolescent health literature emphasizes the importance of healthy stress response and coping behaviors (Garcia, Pintor, Vazquez, & Alvarez‐Zumarraga, ); clinicians should help adolescents recognize their primary coping strategies and offer tools that strengthen positive coping. This has potential to minimize negative mood and indirectly encourage sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…No treatments on the current suicide prevention best practices registries are specifically targeted to the unique needs of this population (Suicide Prevention Resource Center, 2017). One school-based program operating in two Minnesota schools, Project Wings, is specifically targeted to Latinas and offers a series of activities to help students cope with stress; feasibility trials have found reduced stress and depression among participants (Garcia, Pintor, Vazquez, & Alvarez-Zumarraga, 2013). …”
Section: Few Evidence-based Treatment Optionsmentioning
confidence: 99%